2021
DOI: 10.3389/fimmu.2021.661934
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Neutrophil Count as a Predictor of Antituberculosis Therapy Outcomes: A Multicenter Prospective Cohort Study

Abstract: BackgroundNeutrophils have been associated with lung tissue damage in many diseases, including tuberculosis (TB). Whether neutrophil count can serve as a predictor of adverse treatment outcomes is unknown.MethodsWe prospectively assessed 936 patients (172 HIV-seropositive) with culture-confirmed pulmonary TB, enrolled in a multicenter prospective cohort study from different regions in Brazil, from June 2015 to June 2019, and were followed up to two years. TB patients had a baseline visit before treatment (mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…M. tuberculosis -specific CD4 + T cells that express PD1 define a population of T cells that have seen antigen and correlate with mycobacterial load 199 . Similarly, circulating natural killer cell counts decrease during active infection and can be used to track treatment response 200 , whereas a high blood neutrophil count correlates with a negative treatment outcome 201 . Thus, exploiting our understanding of host–pathogen interactions has the potential to yield novel TB diagnostics and biomarkers, but paucibacillary disease and the heterogeneity of the host response remain challenges.…”
Section: Reactivation and Transmissionmentioning
confidence: 99%
“…M. tuberculosis -specific CD4 + T cells that express PD1 define a population of T cells that have seen antigen and correlate with mycobacterial load 199 . Similarly, circulating natural killer cell counts decrease during active infection and can be used to track treatment response 200 , whereas a high blood neutrophil count correlates with a negative treatment outcome 201 . Thus, exploiting our understanding of host–pathogen interactions has the potential to yield novel TB diagnostics and biomarkers, but paucibacillary disease and the heterogeneity of the host response remain challenges.…”
Section: Reactivation and Transmissionmentioning
confidence: 99%
“…In addition, a prospective case-control study which enrolled pulmonary TB patients admitted to the emergency department of a referral TB hospital also found that severe anemia composed a prediction score to infer early mortality, which was defined as death within one week of hospital admission [ 24 ]. In a previous study of our group, we demonstrated that increased neutrophil count prior to ATT initiation was associated with unfavorable treatment outcomes [ 25 ]. Herein, neutrophil count and Hb levels had a negative correlation.…”
Section: Discussionmentioning
confidence: 99%
“…2H, I). Excessive neutrophil recruitment and infection is associated with Mtb replication, tissue damage, and progression of Mtb disease in mice and humans 16,[41][42][43][44][45][46][47] . If the critical role for TH1 responses that is lost in Irgm1 -/mice during Mtb infection is control of Mtb infection and replication in neutrophils, then depletion of neutrophils might prolong survival of Mtb-infected Irgm1 -/mice.…”
Section: Neutrophil Depletion Extends the Survival Of Irgm1 -/Mice Du...mentioning
confidence: 99%